Cost of illness of apathy in Alzheimer's disease. (31st December 2021) - Kruse, Christopher; Maier, Franziska; Bürger, Katharina; Dodel, Richard; Fellgiebel, Andreas; Frölich, Lutz; Klöppel, Stefan; Kornhuber, Johannes; Laske, Christoph; Peters, Oliver; Priller, Josef; Schneider, Anja; et al.
Abstract: Background: Within a 12‐week multicentre randomised controlled trial, standardised data on resource use of patients and their caregivers was collected using the Resource Utilization in Dementia (RUD) instrument. The aim of this study is to evaluate the insufficiently known influence of apathy on resource utilisation in Alzheimer's patients and their caregivers. Method: 107 patients were included in the study. Costs were collected from a societal perspective over a four‐week period and examined depending on the Apathy Evaluation Scale‐Clinician Version (AES‐C). Using the Mann‐Whitney U and Kruskal‐Wallis tests, potential cost drivers were identified in a univariate analysis. Afterwards potential cost drivers for total costs, patient costs and caregiver costs were analysed using a generalised linear model (GLM) with a γ‐distributed dependent variable and log link function. Result: The mean total costs were €3, 069. The mean patient costs were €359 and were mainly related to professional services, hospitalisation and medication. The mean caregiver costs were €2, 711 and were largely caused by informal care with a share of €2, 509. Within the sensitivity analysis, informal care costs decreased to €1, 742 and €903, respectively. The multiple regression analysis showed that Apathy, represented by the AES‐C, is a cost driving factor for total costs and caregiver costs, however not for patient costs. Conclusion: Previous studies have often presented costs as a function of cognitive impairment. The present data show that apathy also has a significant influence on resource utilisation. At the same time, however, it was also shown that this influence was mainly caused by the increased resource use of the caregivers and that the resource use of the patients did not show significant changes.